Isolation, screening, and molecular characterization using 16S rDNA gene of feather-degrading bacteria isolated from poultry soil in Basrah Province, Iraq - NOOR M. AHMED AL-AMERY; NASSIR ABDULLAH ALYOUSIF (Society for Indonesian Biodiversity, 2024)
Abstract. Al-Amery NMA, Alyousif NA. 2024. Isolation, screening, and molecular characterization using 16S rDNA gene of feather-degrading bacteria isolated from poultry soil in Basrah Province, Iraq. Biodiversitas 25: 3217-3226. Bioremediation of feathers based on the production of keratinase enzyme is one of the most promising methods and has gained increasing interest in biotechnology. This study aimed to isolate, identify, and screen the bacteria that can potentially degrade feathers from the soil in Basrah province, Iraq using 16S rDNA gene. Ten soil samples were collected from various poultry fields and 97 bacterial isolates have been isolated from the samples. Seventy-four protease-producing isolates were found among isolates. The highest number of bacterial isolates that were found to be able to break down feathers were B6, E1, F7, M6, and J9 according to the values of keratinase activity were 42.1 U/mL, 29.1 U/mL, 28.8 U/mL, 28.1 U/mL, and 28.1 U/mL, respectively. The isolate B6 was the most promising isolate, because it was the best isolate with a higher value of 42.1 U/mL. Based on the sequencing of the 16S rDNA gene, these 5 isolates were identified as Bacillus amyloliquefaciens, B. subtilis, B. licheniformis, B. subtilis, and B. pumilus, respectively. Eleven bacterial isolates have been reported as new strains and recorded in NCBI GenBank. The current study reported several isolates that have the potential to produce keratinase with different capabilities for the first time in the world.